Profitability of Western European banking systems: panel evidence on structural and cyclical determinants - Rainer Beckmann (Deutsche Bundesbank, 2007)
This paper analyses structural and cyclical determinants of banking profitability in 16 Western European countries. We find that financial structure matters, particularly through the beneficial effect of the capital market orientation in the respective national financial system. Furthermore, higher diversification regarding banks' income sources shows a positive effect. The industry concentration of national banking systems, though, does not significantly affect aggregate profitability. Business cycle effects, in particular lagged GDP growth, display a substantial procyclical impact on bank profits. These results are obtained in a single equation panel framework using the Hausman-Taylor instrument variable estimator. The data set comprises aggregate annual country data and banking group data (commercial banks, cooperative banks and savings banks) over the period 1979-2003.
Keywords: G21; E32; L11; 330; bank profits; financial structure; business cycle; Bank; Rentabilität; Kapitalstruktur; Bankensystem; Finanzmarkt; Konjunktur; Westeuropa